Music-Induced Vibrations in a Concert Hall and a Church - Sebastian MERCHEL; Mehmet Ercan ALTINSOY (Archives of Acoustics)
Sound and vibrations are often perceived via the auditory and tactile senses simultaneously, e.g., in a car or train. During a rock concert, the body vibrates with the rhythm of the music. Even in a concert hall or a church, sound can excite vibrations in the ground or seats. These vibrations might not be perceived separately because they integrate with the other sensory modalities into one multi-modal perception.